Consolidation-acidizing experiments on methane natural gas sediment skeleton - Xu, Zhenqiang; Shen, Kaixiang; Wang, Yingsheng; Wu, Jia; Liu, Pingli; Du, Juan; Huang, Qisheng; Chen, Cai (Frontiers in Energy Research, 2024)
During the development of natural gas hydrates, it is important to ensure the stability of the reservoir. The hydrate reservoirs in the South China Sea are clayey silt sediments, which are prone to sand production and collapse during hydrate dissociation. This study innovatively proposes the idea of consolidation-acidizing for NGH reservoir modification. Based on the core parameters of well A drilling in the Shenhu Sea area of the South China Sea, NGH sediment skeleton samples were artificially prepared. Core sensitivity testing indicates that the NGH reservoir has the potential for acidizing modification. After using tetraethyl orthosilicate to solidify the sample, it was found that Young’s modulus of the sample increased by 58.8%, and the compressive strength increased by 54.78%. Although the porosity decreased by 39.33%, the pores were not completely blocked. After the acidizing experiment, the permeability of the consolidated sample was 2.88 mD, and the porosity increased by 10.63%; The permeability of the unconsolidated sample was 1.86 mD, and the porosity decreased by 10.73%. The CT scan images also showed that the pores of the sample after consolidation-acidizing developed uniformly without significant deformation; The unconsolidated sample undergoes severe deformation and sand production after acidizing. This study demonstrates that the consolidation-acidizing modification method is feasible in clayey silt hydrate reservoirs.